Colon Targeted Delivery Dosage Forms for Probiotics: A Review - Anjasmara, Gede Anom; Hartrianti, Pietradewi; Iswandana, Raditya (Pharmaceutical Sciences and Research, 2023)
Encapsulation was a promising method for protecting probiotics from extreme conditions during their passage through the gastrointestinal tract and delivering probiotics to specific sites in the colon for colonization. Various dosage forms have been used in recent years to encapsulate probiotics to maintain cell viability during processing, storage, and through the digestive tract to provide health benefits. However, research related to the encapsulation of probiotics as the dosage forms for colon-targeted delivery systems was still quite limited to conventional dosage forms due to the sensitivity of probiotics to extreme conditions during the process. This review focuses on various types of dosage forms that are used in colon-targeted delivery systems for commonly used probiotic bacteria. In this review, we discussed the limitations of the current dosage forms used in probiotic encapsulation, along with the latest advancements in colon-targeted delivery systems for probiotic products. This review also covers future perspectives on the potential dosage forms that can effectively maintain probiotic viability and provide specific release in the colon.